METHODOLOGICAL APPROACHES TO TEACHING VOCABULARY THROUGH ETYMOLOGY - Ahundjanov Bahodir Zafarovich (Bright Mind Publishing, 2025)
Vocabulary is not merely a collection of words; it is a key to unlocking meaning, context, and culture in any language. This article delves into methodological approaches to teaching vocabulary through etymology - examining the cognitive, linguistic, and pedagogical implications of using word origins as a tool for deeper learning. Drawing on both theoretical insights and classroom practice, it argues that etymology-based instruction offers more than just memorization: it nurtures language awareness, critical thinking, and intercultural sensitivity.
Keywords: Etymology, vocabulary teaching, word origins, cognitive linguistics, language pedagogy, morphemic analysis, intercultural competence, lexical awareness, comparative linguistics, deep learning.